2013
DOI: 10.4149/gpb_2013010
|View full text |Cite
|
Sign up to set email alerts
|

Maternal restraint stress negatively influences growth capacity of preimplantation mouse embryos

Abstract: Abstract. In our study we investigated the effect of maternal restraint stress on preimplantation embryo development using a mouse model. We exposed hormonally stimulated (superovulated) and unstimulated (i.e. spontaneously ovulating) mouse females to restraint stress for 30 min three times a day during the preimplantation period. The stress exposure caused significant increase in blood plasma corticosterone concentration. Microscopical evaluation of embryos isolated from spontaneously ovulating females showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Our analysis of the blastocyst cell number revealed no significant differences between the blastocysts isolated from the compared groups of females. In our previous study (Burkuš et al 2013), a decreased cell number was observed in the blastocysts isolated from mothers exposed to restraint stress (a heterogenic population of females without any dietetic modeling and with undefined somatic parameters was used in the experiment), and the difference was more prominent in later-stage blastocysts (p < 0.001) than in earlier-stage blastocysts (p < 0.05). Again, the discrepancy between the results could be caused by the different stages of blastocysts analyzed in the two experiments.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our analysis of the blastocyst cell number revealed no significant differences between the blastocysts isolated from the compared groups of females. In our previous study (Burkuš et al 2013), a decreased cell number was observed in the blastocysts isolated from mothers exposed to restraint stress (a heterogenic population of females without any dietetic modeling and with undefined somatic parameters was used in the experiment), and the difference was more prominent in later-stage blastocysts (p < 0.001) than in earlier-stage blastocysts (p < 0.05). Again, the discrepancy between the results could be caused by the different stages of blastocysts analyzed in the two experiments.…”
Section: Discussionmentioning
confidence: 84%
“…In our previous studies we showed that the amount of maternal body fat or maternal restraint stress can significantly affect the quality of oocytes and in vivo developed preimplantation embryos (Burkuš et al 2013(Burkuš et al , 2015Kubandová et al 2014;Fabian et al 2015). In this study, we investigated the effect of stress on blastocyst quality in the context of maternal physiological status.…”
Section: Introductionmentioning
confidence: 97%
“…Adrenaline, cortisol, shear stress, SAPK activation, AMPK activation [3,53,87], maternal malnutrition, genotoxic stress (benzopyrene), hyperosmotic stress, TRP53 activation all slow embryo growth [3]. Interestingly, maternal stress hormones decrease growth of TSC and ESC lineages in the blastocyst [88]. Thus maternal signaling can increase or decrease embryonic growth and potentially have long-term effects.…”
Section: Nutrition and Stress Affects Stem Cells And Reproductionmentioning
confidence: 95%
“…The exposure of mice females to restraint stress resulted in decrease in cell numbers in preimplantation embryos (Burkuš et al. ). Moreover, stress applied in the period of preimplantation development reduced the litter size in mice and hamsters (Wiebold et al.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we demonstrated the negative effect of maternal restraint stress on the development of mouse preimplantation embryos (Burkuš et al. ). We also found the expression of several types of adrenergic receptors in mouse oocytes and preimplantation embryos and showed that activation of these receptors can influence cell proliferation in vitro (Čikoš et al.…”
Section: Introductionmentioning
confidence: 90%